Integration of Firewall Log Data into Accounting Information Systems to Enhance Internal Control and Cyber Threat Detection: A Case Study Using Palo Alto PA820 - Roup, Abdul (Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to evaluate and integrate log data from the Palo Alto PA820 firewall security device into an accounting information system (AIS) to strengthen internal control and enhance early detection of cyber threats. As digital security risks increasingly target accounting data, this integration is expected to provide real-time visibility into network activities that could compromise the confidentiality, integrity, and availability of financial information. A case study approach was conducted in a company that utilizes both the PA820 firewall and a network-based AIS. Data were collected from activity log dashboards, security policy configurations, and GlobalProtect connection records. The results indicate that firewall logs can be effectively incorporated into the AIS audit trail module and are capable of detecting abnormal behaviors such as suspicious login attempts, connections from unfamiliar locations, and exploitation efforts related to the CVE-2024-3400 vulnerability. These findings contribute to the development of more cyber-resilient accounting systems. Keywords: accounting information system, firewall, log data, internal control, Palo Alto, CVE-2024-3400